Principles of Modeling Students in Their Future Professional Activity From Simple to Complex, From Abstract to Accuracy - Eshtemirov Akror Nurmakhmatovich (Genius Publishing Group, 2022)
In this article, the theoretical basis of modeling students in their future professional activities is presented. also quot; in professional activity, the principles of modeling from simple to complex, from abstract to accuracy are theoretically based.
Keywords: Future professional activity; modeling; engineer; designer